2017
DOI: 10.1111/ctr.12951
|View full text |Cite
|
Sign up to set email alerts
|

Early conversion to belatacept after renal transplantation

Abstract: Belatacept is a non-nephrotoxic immunosuppressive agent, which may make it the ideal agent for patients with delayed or slow graft function on calcineurin inhibitors. There are limited data on conversion of patients to belatacept within 6 months of transplantation. Between January 2012 and December 2015, 16 patients were converted to belatacept for delayed or poor graft function (eGFR<30 mL/min/1.73 m , MDRD); three were HIV positive. Conversion protocols were analyzed in patients ≤4 months and 4-6 months post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 9 publications
4
23
0
Order By: Relevance
“…Conversion to belatacept in immunologically higher risk populations, including African Americans and patients with preformed DSA, has been questioned due to the higher observed rates of BPAR with belatacept and the underrepresentation or exclusion of these patients from early phase II and III trials . In our patient cohort, we observed a rejection rate of 9.4% at 1 year following conversion to belatacept, which is in line with previous studies reporting overall rejection rates ranging from 7.0% to 16.7% for patients receiving lymphocyte‐depleting induction . While BPAR is more common following conversion to belatacept compared with CNI continuation, rejection rates are similar to those reported with conversion to mechanistic target of rapamycin (mTOR) inhibitors in the CONVERT and ASCERTAIN trials …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Conversion to belatacept in immunologically higher risk populations, including African Americans and patients with preformed DSA, has been questioned due to the higher observed rates of BPAR with belatacept and the underrepresentation or exclusion of these patients from early phase II and III trials . In our patient cohort, we observed a rejection rate of 9.4% at 1 year following conversion to belatacept, which is in line with previous studies reporting overall rejection rates ranging from 7.0% to 16.7% for patients receiving lymphocyte‐depleting induction . While BPAR is more common following conversion to belatacept compared with CNI continuation, rejection rates are similar to those reported with conversion to mechanistic target of rapamycin (mTOR) inhibitors in the CONVERT and ASCERTAIN trials …”
Section: Discussionsupporting
confidence: 88%
“…In the landmark trial by Vincenti et al, a de novo CNI‐free regimen of belatacept, mycophenolate, and prednisone led to improved composite patient and allograft survival and a higher eGFR at 7‐years compared with a cyclosporine‐based regimen, despite higher rates of biopsy proven acute rejection (BPAR) with belatacept . Subsequent studies evaluated post‐transplant conversion from a CNI to belatacept and observed similar improvements in eGFR with belatacept relative to CNI maintenance, again with higher rates of early rejection …”
Section: Introductionmentioning
confidence: 98%
“…[24][25][26] Similar to previous literature, belatacept recipients experienced higher grades of rejections, but this did not contribute to short-term graft loss, except in one patient, in whom there were adherence concerns. A few studies have previously reported the outcomes of depleting induction in conjunction with belatacept; however, these have been conducted in patients receiving more optimal quality donor kidneys.…”
Section: Discussionsupporting
confidence: 76%
“…These improvement in eGFR of about 6 mL/min. [24][25][26] Similar to previous literature, belatacept recipients experienced higher grades of rejections, but this did not contribute to short-term graft loss, except in one patient, in whom there were adherence concerns. In our study, we also combined depleting induction with steroid withdrawal.…”
Section: Evidence Of Resolving Moderate Pathologic Changes Is Encourasupporting
confidence: 76%
“…For patients unable to change from a boosted HAART regimen, caution should be taken with medication dosing and CNI troughs should be carefully monitored. Belatacept, a novel T‐cell co‐stimulation blocking agent, has been used successfully in HIV‐infected recipients . If larger studies demonstrate safety and efficacy, belatacept may be another choice of immunosuppression in HIV patients on boosted PI‐based HAART.…”
Section: Discussionmentioning
confidence: 99%